Eksistensi pendidikan agama pada mahasiswa sebagai penunjang moral bagi generasi muda - Frasasti, Meilinda (Maliki Interdisciplinary Journal, 2024)
Religious education is a very important education for the younger generation, and is the basic foundation for human life. Religious education teaches to develop mental, moral, and physical strength for the younger generation. By studying religion, we will know many sciences and teachings contained in it, so that it will unite in the soul of the younger generation and make them a moral and civilized generation. However, with the realities that we are now facing, such as the impact of the increasingly advanced globalization era, increasingly sophisticated technology, moral values in the younger generation, especially in students are currently experiencing a very concerning degradation. Students are swept away by the enjoyment of existing technology, so they neglect their obligations as students. Therefore, as the next generation of the nation we have to learn a lot, especially deepening religious teachings, so that we do not get lost and neglectful in doing our obligations as students, , and so that the formation of good morals in students, so that not only the title or education is high, but accompanied by good morals and morals as a support for the future of the nation.